The interaction effect of process parameters on the phase transformation behavior and tensile properties in additive manufacturing of Ni-rich NiTi alloy. (May 2022) - Shi, Guangfeng; Li, Lunxiang; Yu, Zhenglei; Liu, Ruiyao; Sha, Pengwei; Xu, Zezhou; Guo, Yunting; Xi, Rui; Liu, Jiabao; Xin, Renlong; Chen, Lixin; Wang, Xiebin; et al.
Abstract: In this work, response surface methodology (RSM), as a reliable and cheap prediction tool, was developed to establish a quadratic regression model between selective laser melting (SLM) process parameters and the martensite transformation temperatures (MTTs) of SLM-NiTi alloys during SLM process. In the case of martensite start temperature ( M s ) and austenite finish temperature ( A f ), analyzing the result of RSM illustrated that the average error percentage between the predicted and experimental results are within 7.42 ± 0.45% and 3.83 ± 0.23%, respectively. Besides, we show that the interaction of laser power ( P ) and scanning speed ( v ) have a remarkable impact not only on MTTs but also on tensile properties and tensile recovery strain of SLM-fabricated NiTi samples. With the decrease of P and the increase of v, the M s and A f decrease, respectively. The tensile experimental results showed that the group of 150 W samples equipped with high elongation, in which the highest elongation up to 12 ± 0.4%, but the high tensile recovery strain was presented in the 100 W series. This study provided a new-fangled insight for how process parameters modulate phase transformations and mechanical properties in the SLM fabricated NiTi, which can be conducted to target mechanical properties for different applications. Graphical abstract: Unlabelled Image Highlights: Response surface method (RSM) is utilized to predicted the martensitic transformation temperatures (MTTs) successfully. This model is proved that the MTTs of SLM-NiTi alloys are influenced by the interaction effect of process parameter ( P, v ). The interaction effect for process parameters is also linked to uitimate fracture strength and tensile recovery rate.